EKPERIMENTASI PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV MI NW SURALAGA - Abdul Aziz; Hilman (Al-mujahidah, 2026)
Low student interest in learning and the dominance of teachers in the learning process, where information flows only one way without student feedback to the teacher, are the main factors causing poor student learning outcomes. A suitable learning model to facilitate students in the learning process in group settings is the Jigsaw cooperative learning model. The purpose of this study is to determine the effect of the Jigsaw type cooperative learning model on mathematics learning outcomes. The research method used was quasi-experimental with a one-group pretest-posttest design, involving two classes: an experimental class and a control class. Data analysis was conducted through tests for normality, homogeneity, and hypothesis testing using an independent sample t-test with the assistance of SPSS version 25. The results showed an increase in average pretest-posttest scores in both the experimental class (48.6 to 83.45) and the control class (47.76 to 71.38). The t-test result showed a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. The conclusion of this study is that the implementation of the Jigsaw type cooperative learning model has a positive and significant effect on students' mathematics learning outcomes.